Ruling 190: Structure of Islamic Cross Currency Swap (ICCS) - Soualhi, Younes; Zakariyah, Habeebullah; Ashurov, Sharofiddin; Ishak, Muhammad Shahrul Ifwat; Saleh, Abdulmajid Obaid Hasan (Al Rajhi Bank Malaysia, 2025)
The Shariah Board of Al Rajhi Banking & Investment Corporation (Malaysia) Bhd. (“Shariah Board”) in its meeting held on 15/05/1447 H. corresponding to 06/11/2025 G. reviewed a proposal concerning “Structure of Islamic Cross Currency Swap (ICCS) and its attachment “ICCS Underlying Structure”